Influence of language barrier and cultural background in hepatitis B disease knowledge in a Chinese community of Spain - Pocurull, Anna; Collazos, Cristina; Miralpeix, Anna; Tapias, Laura; Wang, Tao; Moreta, María Jose; Mariño, Zoe; Lens, Sabela; Forns, Xavier (Frontiers in Public Health, 2024)
Introduction Hepatitis B infection (HBV) is prevalent in China. Due to language barriers and cultural differences, it is not always straightforward to evaluate disease knowledge in liver clinics. We aimed to assess the awareness on HBV and its mechanisms of transmission in HBV-infected Chinese patients and their household contacts. Methods HBV-infected Chinese patients and their contacts were interviewed by a native Chinese nurse regarding their knowledge on HBV transmission mechanisms, use of preventive measures and vaccination status. Non-Chinese HBV-infected patients and their household contacts served as a control group. Results In total 182 patients and 398 contacts participated with 85 (47%) patients and 240 (60%) contacts being from China. Language barrier was reported in 80% of Chinese patients and 44% of their contacts. Knowledge on parenteral and sexual HBV transmission was high in all patients ( 90%) but Chinese were more aware of vertical transmission than controls (94% vs. 68%; p < 0.01). Regarding the use of preventive measures, Chinese patients were more forewarned in their use to avoid parenteral transmission (93% vs. 74%, p < 0.01). When assessing household contacts, Chinese used preventive measures more frequently than controls for parenteral and sexual transmission (79% vs. 65 and 81% vs. 48%, p < 0.05). Vaccination coverage was slightly lower in Chinese contacts compared to controls (78% vs. 86%, p = 0.05). Conclusion Despite relevant language barriers, Chinese patients are well informed on the mechanisms of HBV transmission. Cultural differences may explain a higher use of preventive measures among the Chinese population. HBV vaccination of household contacts should be reinforced in both groups.